2022
DOI: 10.1177/15593258221130749
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bioactives and Nutra-Pharmaceutical Potential of Supercritical Fluid and Hydro-Distilled Extracted Coriander Leaves Essential Oil

Abstract: The volatiles chemical composition and biological attributes of coriander ( Coriandrum sativum L.) leaves essential oil obtained by two extraction techniques namely supercritical fluid extraction and hydro-distillation is appraised. The coriander essential oil yield (.12%) by hydro-distillation was slightly higher than that of supercritical fluid extraction (.09%). The physico-chemical variables of the essential oil obtained from both the techniques varied in significantly (P < .05). GC-MS analysis identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…These findings revealed a marked influence of the method applied on the composition of the minor compounds [ 71 ]. Abbas et al [ 75 ] reported coriander aerial parts essential oil yield isolated by hydrodistillation was a little higher than the extract obtained by supercritical fluid extraction. However, when compared to the essential oil obtained by hydrodistillation, the extract obtained by supercritical fluid extraction had a higher biological potential due to the presence of a larger number of bioactive compounds.…”
Section: Resultsmentioning
confidence: 99%
“…These findings revealed a marked influence of the method applied on the composition of the minor compounds [ 71 ]. Abbas et al [ 75 ] reported coriander aerial parts essential oil yield isolated by hydrodistillation was a little higher than the extract obtained by supercritical fluid extraction. However, when compared to the essential oil obtained by hydrodistillation, the extract obtained by supercritical fluid extraction had a higher biological potential due to the presence of a larger number of bioactive compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the EO from coriander stems revealed that phytol (61.86%) was the primary component present 101 . EOs from coriander leaves that were extracted using two different procedures and had linalool as the primary component (51.32% and 61.78%, respectively) were analyzed by GC-MS 102 .…”
Section: Discussionmentioning
confidence: 99%
“…Linalool, geranyl acetate, α-terpinene and α-pinene were found to be present in coriander EO, and act as anti-inflammatory agents, as suggested in a prospective study. 70 Traditional uses of Annona muricata leaves have considerable ameliorative benefits due to the presence of terpenoid compounds. The research investigation involved the distillation of essential oils to identify their volatile components.…”
Section: Discussionmentioning
confidence: 99%